Advances in the modification and applications of cellulosic-based materials for wastewater remediation: a review - AbdElAziz A. Nayl; Ahmed I. Abd-Elhamid; Katarína Mosnáčková; Wael A. A. Arafa; Ahmed Hamad Alanazi; Ismail M. Ahmed; Hazim M. Ali; Ashraf A. Aly; Magda Aly Akl; Ahmed Salah Doma; Hisham Fouad Aly; Stefan Bräse (Applied Water Science, 2025)
Abstract Over the decades, the scarcity of fresh water has emerged as the most significant obstacles facing human societies. Many water sources have become threatened by contamination with different types of life-threatening pollutants, representing a major challenge to humans and leading to a shortage of getting safe drinking water. Therefore, many countries and researchers worldwide are trying to unite and overcome these challenges to identify innovative eco-friendly materials and techniques with considerable effectiveness for water purification. Recently, cellulose-based materials have shown considerable results in this field, which have attracted the attention of many scientists due to their unique and promising characterizations, which makes cellulosic material is an excellent substrate to develop attractive materials to treat wastewater. This review focuses on the new approaches in the modification and applications of biodegradable cellulose-based materials in treatment of wastewater and explains the advantages and disadvantages of such materials. On the other hand, this work highlighted the utilization of modified cellulose-based materials on the remediation of wastewater from different heavy metal ions (such as Cu(I,II), Pb(II), Tl, and F(− 1)), oil/water separation, removal of dyes, and removal of other organic pollutants. The review illustrated that cellulose-based materials are promising and effectiveness nanomaterials in its various forms to treat wastewater from different types of pollutants. Moreover, this work highlights the advantages and disadvantages of some applied characterization techniques in addition to the future challenges and prospect of value added of cellulosic-based materials for wastewater remediation.